Analisis SWOT Sebagai Strategi Meningkatkan Daya Saing UMKM Hoki Souvenir - Elinda Dwi Kusuma; Deni Ramdani (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
SWOT analysis is a marketing strategy that can be used in analyzing internal factors and external factors including strengths, weaknesses, opportunities and threats in facing increasingly fierce competition in various business scopes, especially SMEs. This study uses a descriptive qualitative method using primary data based on the results of interviews with the owner of the UMKM Hoki Souvenir. Secondary data in this study were obtained from literature studies from journals, previous research and the internet. The results of this study are that there are weaknesses possessed by UKM Hoki Souvenir which result in threats that arise from outside so that the marketing strategy for UKM Hoki Souvenir still needs to be improved.